The Labor Market Effects of a Refugee Wave: Synthetic Control Method Meets the Mariel Boatlift - Giovanni Peri; Vasil Yasenov (Institute of Labor Economics (IZA), 2017)
We apply the Synthetic Control Method to re-examine the effects of the Mariel Boatlift, a large inflow of Cubans into Miami in 1980, first studied by David Card (1990). This method improves on previous studies by choosing a control group so as to best match Miami's labor market features before the Boatlift. We also provide reliable standard errors for the inference. Using data from the larger and more precise May-ORG Current Population Survey (CPS) one finds no significant departure of wages and employment of low-skilled workers between Miami and its control after 1979. The result is robust to several checks.
Keywords: J3; J61; 330; immigration; wages; mariel boatlift; synthetic control method; measurement error